Impact of the leaner P/Q-type Ca(2+) channel mutation on excitatory synaptic transmission in cerebellar Purkinje cells - Liu, Shaolin (Blackwell Science Inc, 2008)
Loss-of-function mutations in the gene encoding P/Q-type Ca(2+) channels cause cerebellar ataxia in mice and humans, but the underlying mechanism(s) are unknown. These Ca(2+) channels play important roles in regulating both synaptic transmission and intrinsic membrane properties, and defects in either could contribute to ataxia. Our previous work described changes in intrinsic properties and excitability of cerebellar Purkinje cells (PCs) resulting from the leaner mutation, which is known to reduce whole-cell Ca(2+) currents in PCs and cause severe ataxia. Here we describe the impact of this mutation on excitatory synaptic transmission from parallel and climbing fibres (PFs, CFs) to PCs in acute cerebellar slices. We found that in leaner PCs, PF-evoked excitatory postsynaptic currents (PF-EPSCs) are ˜50% smaller, and CF-evoked EPSCs are ˜80% larger, than in wild-type (WT) mice. To investigate whether reduced presynaptic Ca(2+) entry plays a role in attenuating PF-EPSCs in leaner mice, we examined paired-pulse facilitation (PPF). We found that PPF is enhanced in leaner, suggesting that reduced presynaptic Ca(2+) entry reduces neurotransmitter release at these synapses. Short-term plasticity was unchanged at CF–PC synapses, suggesting that CF-EPSCs are larger in leaner PCs because of increased synapse number or postsynaptic sensitivity, rather than enhanced presynaptic Ca(2+) entry. To investigate the functional impact of the observed EPSC changes, we also compared excitatory postsynaptic potentials (EPSPs) elicited by PF and CF stimulation in WT and leaner PCs. Importantly, we found that despite pronounced changes in PF- and CF-EPSCs, evoked EPSPs in leaner mice are very similar to those observed in WT animals. These results suggest that changes in synaptic currents and intrinsic properties of PCs produced by the leaner mutation together maintain PC responsiveness to excitatory synaptic inputs. They also implicate other consequences of the leaner mutation as causes of abnormal cerebellar motor control in mutant mice.